KAJIAN AKTIVITAS ANTIBAKTERI PRODUK ETANOLISIS DARI CAMPURAN MINYAK INTI SAWIT (Elaeis quineensis Jacq.) DAN MINYAK BIJI MENGKUDU (Morinda citrifolia L.) - Murhadi Murhadi; Suharyono AS Suharyono AS (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2008)
The objective of this research was to measure antibacterial activities of ethanolysis products that produced through ethanolysis reaction of mixture of palm kernel oil (PKO) and Morinda seeds oil (25:1 and 50:1, w/w) in ethanol solution contained 1% NaOH (v/w based on oil weight) at ratio of 5 : 6 (b/v) and shaken on a shaker (300 rpm, room temp.) for 3, 6, 9 and 12 minutes. Fractionation of ethanolysis products using absolute ethanol (1:3; v/v) and centrifuged at 4.000 rpm for 30 min, yielding Fraction 1 (upper layer) and Fraction 2 (lower layer). Generally, all ethanolysis products showed antibacterial activities against four test bacteria (E. coli, S. aureus, B. cereus and S. enteritidis) at range of d values (mm) from 0,93 (B. cereus; 3 min) up to 3,87 (E. coli; 9 min). Fraction 1 showed the highest antibacterial activity with d values (mm) from 1,20 (B. cereus; 9 min) up to 5,63 (E. coli; 9 min), while Fraction 2 for all treatments had no antibacterial activity, relativelly. Ethanolysis products and its fraction (Fraction 1) were resulted from ethanolysis reaction for 6 and 9 min showed higher antibacterial activities than those for 3 and 12 min. Keywords: Antibacterial activities, ethanolysis product, Morinda seeds oil, PKO